The Cambridge handbook of methods in conversation analysis - Robinson, Jeffrey D.; Clift, Rebecca; Kendrick, Kobin H.; Raymond, Chase Wesley (Cambridge handbooks in language and linguistics, 2024)
Conversation Analysis (CA) is the preeminent method for the detailed study of human social interaction. Bringing together thirty-four chapters written by a team of world-renowned experts, this handbook represents the first comprehensive overview of CA methods. Topics include how to collect, manage and transcribe data; how to explore data in search of possible phenomena; how to form and develop collections of phenomena; how to use different types of evidence to analyze data; how to code and quantify interaction; and how to apply, publish, and communicate findings to those who stand to benefit from them. Methods are introduced clearly and discussed in detail, with examples from various languages and cultures used to illustrate the application of CA to diverse settings. Comprehensive yet accessible, it is essential reading for researchers and advanced students in disciplines such as linguistics, sociology, anthropology, communication, and psychology